Revitalisasi Civil Society Melalui Teologi Sosial Pasca Dua Dasawarsa Reformasi - Muwaffiqillah, Moch. (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
This article discusses the importance of developing social theology to revitalize civil society. After two decades of reform, many people have stated that Indonesia's civil society was slowly fading. It was worried that it would reduce the power of democracy previously fought by all elements of society. The access opened to political articulation for political Islam groups is alleged to be the main reason. Islamic political parties or Islamic mass-based political parties are more attractive to Islamic activists. The articulation of Islam is finally understood only as a search for power accommodated in a subordinating manner. We must respect the participation of Nahdlatul 'Ulama and Muhammadiyah in taking part as a civil society power, especially during the New Order era, in which the articulation of Islam socially and culturally seems very strong. This is the bibliographical research with the method of meta-analysis or meta-synthesis. This meta-synthesis explains several syntheses that originate from the convergence of various qualitative reports that produce new interpretations. This research results in the importance of developing and spreading social theology in Muslim society. Social theology is understood as a belief that is in favor of humanity. This theology places the defense of society as the main thing. In this way, it is essential to develop social theology so that civil society always grows and develops alongside Indonesian democracy. The novelty of this research is the theological synthesis in developing Islamic social movements in making civil society.